Attitude Of Medical Personnel On The Implementation Of EMR (Electronic Medical Record) In Dental & Oral Hospital of Bhakti Wiyata Health Sciences Institute (RSGM IIK Bhakta) Kediri - Ainayah, Aulia Nuur; Sukadiono, Sukadiono; Festi W., Pipit (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2025)
This study explores the implementation of Electronic Medical Records (EMR) at RSGM IIK Bhakti Wiyata Kediri, focusing on medical personnel’s attitudes and the factors influencing adoption, such as knowledge, training, and support. Qualitative research was conducted through structured interviews with four informants (two dentists and two dental nurses) who had experience using the EMR system based on the Health Information Technology System (HINTS) application. The findings indicate that EMR has improved healthcare efficiency by enhancing patient data access and supporting better coordination among medical personnel. However, challenges such as slow internet connections, unstable servers, and occasional system errors hinder its full potential. Resistance to EMR adoption, primarily due to inadequate training, was also noted. Although most medical personnel expressed positive attitudes towards EMR, concerns regarding data security, including potential breaches and input errors, were significant. The study recommends addressing these issues by enhancing network infrastructure, improving server reliability, and providing more comprehensive training and technical support. Additionally, periodic system evaluations are suggested to ensure its effectiveness. These improvements are essential for increasing user confidence and optimizing EMR’s contribution to healthcare quality at RSGM IIK Bhakti Wiyata Kediri, supporting the broader digital transformation of healthcare in Indonesia.